A sensitive period for the induction of host plant preference in a generalist herbivorous insect. (November 2020) - Lhomme, Patrick; Khallaf, Mohammed; Larsson, Mattias; Anderson, Peter
Abstract : Many species use early life sensory experiences to guide phenotypic plasticity and facilitate decision making during later adult settlement in new habitats or location of suitable resources. However, only some of the available sensory information in the environment is relevant for future decision making and, in addition, it may only be informative during certain times during development. This means that sampling of environmental information that should be retained to adulthood could be limited to certain sensitive periods. In the polyphagous moth Spodoptera littoralis, recent studies have demonstrated that adult females exhibit an innate preference hierarchy for certain plants that can be modulated by olfactory experience during the larval stage. This olfactory-driven phenotypic plasticity requires that information about plant quality is transferred over the full metamorphosis. However, the timing of information acquisition that affects adult behaviour and whether there is a sensitive period for the sensory experience inducing host plant preferences are not known. In this study, we tested whether experience used by adult females during host plant choice was acquired during early or later larval stages and whether adult females can retain larval experience from only one or from sequential feeding events on different plants. We found that only plant feeding experience during the later larval stages induced a host plant preference shift in adult females. Furthermore, our experiments demonstrated that when given an artificial diet in the later larval stage, adult females relied on their innate plant preference hierarchy even if they had feeding experience from a host plant in the early stages. The existence of a sensitive period during late larval stages may be constrained not only by neural development or limitations, but also by ecological factors affecting when the larval experience is most reliable for adult decisions. Highlights: Larval experience affects adult moth host plant decisions. There is a sensitive period for host plant cue transfer over the full metamorphosis. Only experience at late larval instars affects adult host plant choice decisions. Adults use innate preference when exposed to early instar plant experience.